In vitro pharmacological effects of peficitinib on lymphocyte activation: a potential treatment for systemic sclerosis with JAK inhibitors. (25th November 2019) - Kitanaga, Yukihiro; Imamura, Emiko; Nakahara, Yutaka; Fukahori, Hidehiko; Fujii, Yasutomo; Kubo, Satoshi; Nakayamada, Shingo; Tanaka, Yoshiya
Abstract: Objectives: Peficitinib, a novel Janus kinase (JAK) inhibitor, demonstrated promising results in treating RA in phase 3 clinical trials. This in vitro study was undertaken to characterize the pharmacological properties of peficitinib and investigate the involvement of JAK and signal transducer and activator of transcription (STAT) pathways in the pathological processes of SSc, which is also an autoimmune disease. Methods: Phosphorylation levels of STAT molecules were assessed in peripheral blood mononuclear cells collected from patients with RA or SSc and healthy subjects, and in skin specimens obtained from 19 patients with SSc. In vitro inhibition of STAT phosphorylation and cytokine/chemokine production by peficitinib, tofacitinib and baricitinib were also characterized. Results: Higher spontaneous STAT1 or STAT3 phosphorylation was observed in peripheral T-cells and monocytes from patients with RA and SSc compared with healthy subjects. In skin sections from patients with SSc, phosphorylated STAT3–positive cells were found in almost all cases, irrespective of disease subtype or patient characteristics. Conversely, phosphorylated STAT1-positive cells were observed only in samples from untreated patients with diffuse disease of short duration. Peficitinib inhibited STAT phosphorylation induced by various cytokines, with comparable efficacy to tofacitinib and baricitinib. Peficitinib also suppressed cytokine and chemokine production by peripheral blood mononuclear cells and skin fibroblasts. Conclusion: Our results suggest that JAK/STAT pathways are constitutively activated in SSc and RA, and that the JAK inhibitor may represent a novel therapeutic option for SSc.